2010
DOI: 10.1021/jf100002v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Quantitation of Six Phenolic Amides inAmaranthusspp.

Abstract: Cinnamoylphenethylamines are phenolic amides in which cinnamic acid provides the acid moiety and phenethylamine the amine moiety. Single ion monitoring (SIM) in LC-MS was performed on amaranth leaf extracts. Masses corresponding to sets of regioisomers, including previously reported compounds, were examined. Six peaks were detected and their corresponding standards synthesized for a quantitative LC-MS/MS investigation of cinnamoylphenethylamines in amaranth. Four cinnamoylphenethylamines (caffeoyltyramine, fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Flavonoids, hydroxybenzoic acids, hydroxycinnamic acids and hydroxycinnamyl amides were detected in the young aerial parts of Amaranthus genotypes [17]. Perdesen et al [18] reported phenolic amides in other varieties of the Amaranthus genus ( A. hypochondriacus and A. mantegazzianus ). Hydroacetonic extracts have shown the greatest diversity of secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids, hydroxybenzoic acids, hydroxycinnamic acids and hydroxycinnamyl amides were detected in the young aerial parts of Amaranthus genotypes [17]. Perdesen et al [18] reported phenolic amides in other varieties of the Amaranthus genus ( A. hypochondriacus and A. mantegazzianus ). Hydroacetonic extracts have shown the greatest diversity of secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Amaranth grains have an excellent nutritional quality; they contain approximately 15% protein with an adequate balance of aminoacids, high lysine content, 60% starch and 8% fat, besides minerals and dietary fiber [5]. Polyphenolic compounds, such as phenolic acids and flavonoids, have been characterized in amaranth grains [6]. Furthermore, amaranth grains are considered to be an important source of food for celiac patients, since they are gluten-free [7].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent product ion scans indicated that this peak was likely a derivative of coumaric acid, and its mass (m/z = 284), combined with the function of genes induced by WtsE, led us to speculate that the peak at retention time = 7.1 min was CouTyr. Genuine CouTyr (para-N-transcoumaroyl tyramine) was synthesized (Pedersen et al, 2010) and used as an authentic standard to investigate the identity of the m/z = 284 peak. Comparison of retention time, precursor ion mass, and four precursor-product ion mass transitions (284→146.9, 284→118.8, 284→91.2, and 284→77.1; Supplemental Table S2) confirmed that the peak induced in DC283-induced leaves was CouTyr.…”
Section: Coutyr Induction By Wtse In Maizementioning
confidence: 99%